COVID-19: Radiologic Report of Two Cases: COVID-19: Relato Radiológico de Dois Casos - Matos, António Pedro; Dias, João Lopes; Sardinha, José (Gazeta Médica, 2020)
The world spread of the infection and pandemic of SARS-CoV-2, had a significant social and economic impact, as well as in health systems. Through two case reports, the role of Radiology will be reviewed and discussed. In each clinical scenario the computed tomography findings will be discussed. It is important that all medical personnel are aware of the role of Radiology, namely the computed tomography studies for the diagnosis of SARS-CoV-2 pneumonia. For the radiologists it is imperative to recognize the typical patterns of this disease.